Environmental friendly warp yarn coating from feather wastes with enhanced toughness and tenacity via thiol-ene click chemistry grafting modification - Xing Pan; Daen Qin; Kaili Song; Aixue Dong (Bioresources and Bioprocessing)
Abstract The development of biodegradable and environmental friendly wrap sizing agent is beneficial for reducing the impact of textile desizing effluent on environment. In this work, green and biodegradable keratin sizing agent with enhanced toughness and tenacity was prepared by adjusting side chain tails structure via thiol-ene click chemistry grafting modification for warp yarn slashing against film thermal-embrittlement and fracture during weaving. Feather keratin from waste feather has become an attractive target to replace petroleum-based Poly (vinyl alcohol) sizes due to its easy film-forming ability, excellent adhesive property, biodegradability and low cost. However, keratin yarn coating showed brittleness and easily peeled off from weaving yarn which highly restrict its application. Thus, polymer branched side chain tails with a structure that similar to the wrap yarn was grafted onto keratin molecular chain by utilizing its distinctive thio group as anchor point by means of click chemistry. The results showed that grafting modification could obviously improve the adhesiveness of keratin sizing by the principle of similarity compatibility. The sizing performance, desizing performance as well as its degradability were comprehensively studied. Successful utilization of modified keratin sizes will bring opportunities for the green and sustainable development of textile industry. Graphical Abstract